Role CT imaging for Cancer Diagnosis by Determining Sensitivity and Specificity: 144 Cancer Cases in Tobruk, Libya - Saad Younis,; Emayof, Mardeya (AlQalam Journal of Medical and Applied Sciences, 2024)
Computed tomography (CT) has emerged as a highly accurate and the most effective technique for detecting and diagnosing various types of cancer. It also aids in evaluating the cancer's stage, size, and form. CT has become the mainstay for cancer detection in Libya, where cost and accessibility are the primary factors determining the modality for diagnostic purposes. The study aims to evaluate the role of CT by correlating the CT scan results with histological findings and determining its sensitivity and specificity in diagnosing various cancers. The study was conducted on 144 patients who underwent CT scans between January 2023 and March 2024. The age range of 31–40 years had the highest percentage of cases, with 39 (27.08%). A CT scan showed 98.52% sensitivity and 87.50% specificity, demonstrating high accuracy in identifying malignant and benign cases. The precision and accuracy of CT scans were 99.25% and 97.91%, respectively. This study demonstrates that CT is highly sensitive in detecting cancers, making diagnoses, and particularly in identifying its morphology and type, estimating whether it is benign or malignant, and identifying any other associated findings with high sensitivity and specificity. تعتبر فحوصات التصوير المقطعي المحوسب تقنيات عالية الدقة يتم إجراؤها للكشف عن السرطان وتشخيصه. وقد أصبح التصوير المقطعي المحوسب الدعامة الأساسية للكشف عن السرطان في ليبيا، حيث تعد التكلفة وإمكانية الوصول من العوامل الأساسية التي تحدد طريقة التشخيص. تهدف الدراسة إلى تقييم دور التصوير المقطعي المحوسب من خلال ربط نتائج التصوير المقطعي المحوسب بالنتائج النسيجية وتحديد حساسيته ونوعيته في تشخيص أنواع مختلفة من السرطان. أجريت الدراسة على 144 مريضًا خضعوا لفحوصات التصوير المقطعي المحوسب بين يناير 2023 ومارس 2024. وكان لدى الفئة العمرية 31-40 عامًا أعلى نسبة من الحالات، حيث بلغ عدد الحالات 39 حالة (27.08%). وأظهر فحص التصوير المقطعي المحوسب حساسية بنسبة 98.52% وخصوصية بنسبة 87.50%، مما يدل على دقة عالية في تحديد الحالات الخبيثة والحميدة. بلغت دقة وضبط الأشعة المقطعية 99.25% و97.91% على التوالي. وتوضح هذه الدراسة أن الأشعة المقطعية شديدة الحساسية في اكتشاف السرطانات وتشخيصها، وخاصة في تحديد شكلها ونوعها، وتقدير ما إذا كانت حميدة أم خبيثة، وتحديد أي نتائج أخرى مرتبطة بها بحساسية وخصوصية عالية